Catastrophic Intracranial Hemorrhage as a Presenting Feature of Juvenile Polyarteritis Nodosa. (June 2014) - Srinivasaraghavan, Rangan; Krishnamurthy, Sriram; Mahadevan, Subramanian
Intracranial hemorrhage has been rarely reported during the course of polyarteritis nodosa. We describe a 6-year-old boy who presented with fever, altered sensorium, skin rash, hypertension, and catastrophic intracranial hemorrhage. After surgical evacuation of the intracranial hematoma, he underwent a computerized tomography angiogram that showed narrowing of the right anterior cerebral artery. Skin biopsy showed small vessel vasculitis. Nerve conduction studies were suggestive of mononeuritis multiplex. He was diagnosed as polyarteritis nodosa and managed with immunosuppressants, to which he responded favorably. The most interesting aspect of the child's presentation was the catastrophic onset of altered sensorium with raised intracranial pressure, which was a diagnostic challenge. The mechanisms of intracranial hemorrhage in polyarteritis nodosa and a review of the literature are discussed. The authors emphasize that it is important to recognize intracranial hemorrhage as a life-threatening complication in children with polyarteritis nodosa to institute timely therapy.